Economic evaluation of PRIMROSE: a trial-based analysis of an early childhood intervention to prevent obesity - Döring, Nora; Zethraeus, Niklas; Tynelius, Per; De Munter, Jeroen; Sonntag, Diana; Rasmussen, Finn (Frontiers in endocrinology, 2018)
Background: Childhood obesity is a major clinical and economic health concern. Alongside the clinical understanding of obesity, there is a growing interest in designing and implementing interventions that are worth their money given the scarce resources in the health care sector. This study is one of the first efforts to provide evidence by assessing the effects and costs of a population based primary prevention intervention targeting pre-school children attending child health centers in Sweden. Methods The economic evaluation is based on the PRIMROSE cluster-randomized controlled trial aiming to establish healthy eating and physical activity among preschool children (9-48 months of age) through motivational interviewing applied by trained nurses at child health centers. The cost-effectiveness is assessed over the trial period from a societal perspective. The primary outcome was BMI at age four. Cost data was prospectively collected alongside the trial. Scenario analyses were carried out to identify uncertainty. Results: The estimated additional mean total costs of the PRIMROSE intervention were 342 Euro (95% CI: 334; 348) per child. During preschool years direct costs mainly consist of training costs and costs for the additional time used by nurses to implement the intervention compared to usual care. Early indirect costs mainly consist of parents’ absence from work due to their participation in the intervention. The incremental cost-effectiveness ratio in the base case analysis was 3109 Euro per 1 BMI unit prevented. Conclusion: We cannot provide evidence that the PRIMROSE intervention is cost-effective given the uncertainty in the effect measure. Until further evidence is provided, we recommend resources to be spent elsewhere within the field of obesity prevention. Furthermore, to achieve valid and reliable cost-effectiveness results, the economic evaluation of obesity prevention programs in early childhood should incorporate the life time impact to capture all relevant costs and health effects.